Efficiency and Productivity of the Agricultural Sector in Supporting Indonesia's Food Security - Aisyah Anjani Putri Siregar; Budiasih (Jurnal Ilmu Ekonomi Terapan, 2026)
Objective: The worsening food security situation and the declining output, measured by the added value of the agricultural sector, a sector that plays a crucial role in providing food for the community, given its significant natural capital, raise questions about its performance. Therefore, this study aims to measure technical efficiency and total productivity in the agricultural sector and analyze their impact on food security in Indonesia. Design/Methods/Approach: To support the analysis, this study uses secondary panel data used that obtained from the Central Statistics Agency (BPS) and the National Food Agency (BPN), which will then be analyzed using Stochastic Frontier Analysis (SFA) and panel data regression. Findings: The findings indicate technical inefficiency in the agricultural sector, with an average technical efficiency categorized as medium. Meanwhile, agricultural productivity across regions is known to be uneven, with higher agricultural productivity in western Indonesia dominated by higher agricultural productivity. A large gap was found between the highest and lowest values ​​of technical efficiency and productivity in the agricultural sector, with significant gaps in agricultural output and input between the western and eastern regions. Technical efficiency was found to have a significant positive effect, while productivity had a significant negative effect on food security. Originality/Value: This study can complement research analyzing factors influencing food security in Indonesia from the perspective of production performance that seen from technical efficiency and total productivity, which is still rarely discussed, especially in Indonesia. Practical/Policy implication: The policies that can be suggested based on this research are the need for equitable distribution of agriculture across all regions in Indonesia, both in terms of input and output, improvement of agricultural facilities, extension, mentoring and increased education so that this can improve the quality of farmers in the future, which will also have an impact on increasing technical efficiency and productivity in the agricultural sector which is necessary for achieving food security in Indonesia.